1978
DOI: 10.1063/1.324676
|View full text |Cite
|
Sign up to set email alerts
|

A study of two-stage ion-beam optics

Abstract: Ion-beam optics of a two-stage electrostatic accelerator (i.e., the extraction-accel-decel column) is studied by three approaches: (i) a linear optics analytic solution based on the paraxial equations which account for lens effects and beam space charge, (ii) a nonlinear optics solution based on the Poisson-Vlasov equations and including the two-dimensional source-plasma sheath, and (iii) a 60-kV single-beamlet experimental study. Principal results are that in certain operating modes, the minimum beam divergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…4 In the source plasma, the ions are supposed to be well thermalized and thus the perpendicular component poses as an intrinsic divergence against the acceleration voltage. We assumed the ion temperature in the source plasma to be 0.4 eV ͑Ref.…”
Section: Theoretical Methods For An Optics Analysismentioning
confidence: 99%
“…4 In the source plasma, the ions are supposed to be well thermalized and thus the perpendicular component poses as an intrinsic divergence against the acceleration voltage. We assumed the ion temperature in the source plasma to be 0.4 eV ͑Ref.…”
Section: Theoretical Methods For An Optics Analysismentioning
confidence: 99%
“…Divergence of a space charge limited ionbeam has been estimated by Coupland et al, 19 Ray et al, 20 and Kim et al 18 (more references therein). It was analytically derived and experimentally demonstrated that a minimum beam divergence is achieved when j j max /2.14.…”
Section: Elementary Model For Optimum Beam Extractionmentioning
confidence: 98%
“…3 the lens corresponding to the second grid is either convergent or divergent depending on the relative strength of the electric field in the first and second gap. When the field is weaker in the first gap than in the second (E 1 < E 2 ), the lens is converging, hence a flatter shape of the plasma sheath (and consequently a higher perveance ratio) is required to obtain a collimated jet, whereas if the contrary happens (E 1 > E 2 ), the plasma sheath needs to penetrate more into the plasma to produce more converging ion trajectories to compensate the presence of two diverging lens; this causes a reduction of perveance and hence a reduction of the total extracted current [34].…”
Section: Limits Of Applicability Of Dual Stage Ion Optics On Giementioning
confidence: 99%
“…This change in optimal perveance can be studied as a function of the ratio of the potential drop applied to the acceleration stage to the one applied in the extraction stage. To do so, the analytical model developed by Kim, Whealton, and Schilling [34] will be used. According to this model, the beam divergence can be expressed as…”
Section: Limits Of Applicability Of Dual Stage Ion Optics On Giementioning
confidence: 99%